Leached Salt Cavern Design Using a Fracture Criterion for Rock Salt (81ddea75-bb8e-4c9d-8bc7-d9299dc4873e) - Dale S. Preece (International Conference on Ground Control in Mining, 1984)
In 1975 Congress passed the Energy Conservation Act to establish a U. S. Strategic Petroleum Reserve (SPR) with a capacity of 750 million barrels of crude oil. The most economic storage medium was determined to be salt caverns leached in salt domes in Louisiana and Texas. Salt caverns existed at several sites when the reserve was created. These were obtained by the U. S. Department of Energy (DOE) and used to initiate SPR oil storage. In order to meet the storage capacity approved by Congress, new caverns also had to be leached. To support the resulting design effort, finite element computer program have been used to determine the creep closure and structural stability of salt caverns. Using site specific material properties including creep models, elastic moduli and fracture data, the finite element analyses have replaced earlier empirical approaches to cavern design. This report presents results of such finite element analyses to determine the best cavern roof shape and the minium pillar to dimeter ratio. , P/D. These numerical predictions indicate that the current cavern design is safe.